Sosialisasi Penerapan Sistem Informasi Dokumen Perencanaan Berbasis Web di Bappeda Gianyar - I Nyoman Purnama; Ida Bagus Kresna Sudiatmika (Yayasan Literasi Sains Indonesia, 2022)
Document management of an institution/organization is very important to do. Documents are not managed properly, resulting in reduced work efficiency. The Regional Development Planning Agency or Bappeda Gianyar is a Regional Apparatus Organization in Gianyar Regency - Bali, which is tasked with coordinating the preparation, control and evaluation of the implementation of regional development plans (RPD). Collection and recording of planning documents in the form of softcopies from Regional Apparatus Organizations sent via Whatsapp to different employees in the Program Sector, to allow the existence of these softcopies to be scattered, and also when there is a hardcopy of planning document borrowing to the Program Preparation Division, the recording of the loan is not recorded so well that it would be difficult to trace. In this community service, a Planning Document Information System was designed which aims to serve as a forum for the management of planning documents managed by Bappeda also Research and Development of Gianyar Regency. In order to provide an understanding in terms of business processes and workflows of the system that has been built, in this community service training/socialization of the use of the planning document system is held. So it is hoped that after the socialization of the use of the planning document system, it can provide convenience and work efficiency for state officials in managing planning documents.